The prevalence of musculoskeletal disorders among dentists in the Czech Republic - Sustová, Zdenka; Hodacová, Lenka; Kapitán, Martin (Acta medica (Hradec Kralove), 2013)
The aim of this study was to determine the prevalence of musculoskeletal problems among Czech dentists and to analyze the factors that affect these disorders. Information was gathered through questionnaire completed by 581 physicians. The questionnaire ascertained general information about physicians including their work habits and the characteristics of their work environment along with the occurrence of musculoskeletal problems as well as their intensity. In the past year the occurrence of at least mild difficulties associated with the locomotive system was reported by 96.9% of dentists surveyed (n = 557), with 66.3% of respondents (n = 381) reporting difficulties ofa moderate or major nature. Most respondents of both sexes indicated neck pain. A statistically significant correlation with the occurrence of musculoskeletal complaints of medium and major intensity was demonstrated for the following factors: sex, age, running a private practice, past injury or musculoskeletal diseases, and the perception of work as psychologically demanding. Musculoskeletal disorders in dentists in Czech Republic are relatively frequent and serious health problem. The causes of these diseases must be identified and appropriate preventive interventions undertaken that will contribute to a reduction in the incidence of these problems.
Keywords: Surveys and Questionnaires; Humans; Dentists; lidé středního věku; muskuloskeletální nemoci; Occupational Diseases; prevalence; Female; Aged; mladý dospělý; dospělí; nemoci z povolání; senioři; lidé; průzkumy a dotazníky; Adult; ženské pohlaví; Male; Middle Aged; zubní lékaři; Czech Republic; Aged, 80 and over; Musculoskeletal Diseases; Young Adult; Prevalence; senioři nad 80 let; Česká republika; mužské pohlaví